2013
DOI: 10.1534/g3.113.008664
|View full text |Cite
|
Sign up to set email alerts
|

Mated Progeny Production Is a Biomarker of Aging inCaenorhabditis elegans

Abstract: The relationships between reproduction and aging are important for understanding the mechanisms of aging and evaluating evolutionary theories of aging. To investigate the effects of progeny production on reproductive and somatic aging, we conducted longitudinal studies of Caenorhabditis elegans hermaphrodites. For mated wild-type animals that were not sperm limited and survived past the end of the reproductive period, high levels of cross-progeny production were positively correlated with delayed reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 75 publications
6
57
0
Order By: Relevance
“…Fourth, we evaluated nutritional history and somatic investment through cross-sectional body size (Pincus et al, 2011; Hulme et al, 2010). Fifth, we quantified reproductive output and investment through the number of oocytes laid (Huang et al, 2004; Pickett et al, 2013). These measurements were all performed via custom, fully automated image segmentation and analysis software (Figure 1C and D; see Methods and Resources).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, we evaluated nutritional history and somatic investment through cross-sectional body size (Pincus et al, 2011; Hulme et al, 2010). Fifth, we quantified reproductive output and investment through the number of oocytes laid (Huang et al, 2004; Pickett et al, 2013). These measurements were all performed via custom, fully automated image segmentation and analysis software (Figure 1C and D; see Methods and Resources).…”
Section: Resultsmentioning
confidence: 99%
“…Third, we also measure declining tissue organization through quantitative measurements of textural order and disorder in brightfield images, which has been shown to correlate with lifespan (Herndon et al, 2002; Johnston et al, 2008; Shamir et al, 2009; Pincus et al, 2011). Fourth, C. elegans reproductive output has also been identified as a biomarker of aging and has been shown to decrease with age (Pickett et al, 2013). While Huang et al found no correlation between reproduction and lifespan was found in unmated, and hence sperm-limited, hermaphrodite C. elegans (Huang et al, 2004), we here examine the temperature-sensitive sterile strain spe-9 , which lays unfertilized oocytes, and may thus not be sperm-limited in the same way.…”
Section: Methods and Resourcesmentioning
confidence: 99%
“…In C. elegans , it has been shown that the major source of lifespan variability is different pathogenicity from individual to individual [49]. Furthermore, a recent study revealed that in C. elegans, the production of cross progeny production through Day 4 is an early-stage biomarker of longevity [50]. Interestingly, microRNA reporters ( mir-71 ::GFP, mir-246 ::GFP and mir-239 ::GFP) can also be used to predict lifespan in C. elegans [51].…”
Section: Discussionmentioning
confidence: 99%
“…Like many other physiological systems, the reproductive system of C. elegans undergoes age‐dependent changes (Figure ). The rate of reproduction significantly decreases with age, and the structure of the reproductive system deteriorates (Garigan et al, ; Hughes, Evason, Xiong, & Kornfeld, ; Luo, Kleemann, Ashraf, Shaw, & Murphy, ; McGee, Day, Graham, & Melov, ; Pickett, Dietrich, Chen, Xiong, & Kornfeld, ). As C. elegans is a self‐fertile hermaphrodite with a limited number of sperm (Ward & Carrel, ), sperm shortage is one of the reasons for reduced progeny at an early age.…”
Section: Age‐dependent Changesmentioning
confidence: 99%
“…For example, worms that display fast locomotion during early adulthood (Hahm et al, ; Huang et al, ; Pincus et al, ) or maintain their youth speed in middle age (Hsu, Feng, Hsieh, & Xu, ) tend to have longer lifespans compared with slow‐moving worms. The rate of pharyngeal pumping and the number of progeny after mating also positively correlate with remaining lifespan (Huang et al, ; Pickett et al, ). Second, nucleolar size has a negative correlation with longevity (Tiku et al, ).…”
Section: Potential Biomarkers Of Agingmentioning
confidence: 99%